CD16 and Siglec expression refine the phenotypic heterogeneity of steady-state myeloid-derived suppressor cells - St. Laurent, Chris D.; Jame-Chenarboo, Zeinab; Beck, Alyssa E.; Stubblefield, Stacey; Duan, Shiteng; Sigal, Darren; Macauley, Matthew S. (Frontiers in Oncology, 2025)
BackgroundPolymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) mediate cancer immune suppression by promoting an immunosuppressive microenvironment that inhibits effective anti-tumor immunity. However, they are still a poorly understood, heterogeneous mix of neutrophil subsets. This study aims to determine the Siglec expression profile on several neutrophil subsets and assess their immunosuppressive ability.MethodsWe identified CD16high and CD16low neutrophil subsets from the low-density fractions of human peripheral blood and compared them to high-density neutrophils. We profiled the expression of the entire family of Siglecs on these three key neutrophil populations under steady-state conditions in healthy subjects as well as cancer patients. Moreover, the ability of these populations, isolated from healthy subjects, to suppress T cell proliferation was assessed.ResultsTwo distinct subpopulations were investigated within the low-density fraction of human peripheral blood (CD15+CD66b+CD16low and CD15+CD66b+CD16high) and compared to high-density neutrophils (CD15+CD66b+CD16high). We found that in addition to CD33 (Siglec-3), Siglec-5/-14, -7, and -9, are differentially expressed on the CD16low and CD16high low-density subsets in both healthy, steady-state subjects, and cancer patients. Upregulated expression of CD33 on the CD16low cells led to the initial speculation that they are MDSCs. As the differential expression of Siglec-9 between these two populations was striking, we used CD16 and Siglec-9 double staining to quantify these populations, which demonstrated that the CD16lowSiglec-9low population is greatly upregulated in cancer patients. The CD16high low-density and high-density neutrophils, but not the CD16low low-density neutrophils from healthy subjects, inhibited T cell proliferation, indicating that the CD16lowSiglec-9low population are not MDSCs.ConclusionsThese results demonstrate that Siglecs are differentially expressed on neutrophil subsets, and along with CD16, may be used to help further define what is a PMN-MDSC. Consistent with current observations by others, PMN-MDSCs may encompass an array of neutrophil subtypes, including low-density neutrophils, and point to the need for more work to precisely define the genetic signatures of PMN-MDSCs.